Analisis Bibliometrik Teknologi dalam Pembelajaran Fisika - FIkri Muhardi; Ira Nofita Sari; Lia Angraeni (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
In general, technology is defined as a branch of science that studies how to make tools and how to process and extract goods to overcome various unique challenges and improve human power in general. This study uses bibliometric analysis, bibliometric analysis techniques are used to examine and cite 27 publications related to the use of technology in physics education published between 2014 and 2024. This study uses bibliometric techniques as a form of qualitative descriptive research. This study uses the Publish or Perish, Mandeley and VosViewer software programs, and Publish or Perish is used in the data search process for this study. The number of publications in the last 10 years in 2014-2024 on technology in physics learning indexed by scholars in 2014 there was 1 publication in 2015 there were no published articles, in 2016 it reached 1 publication, then in 2017 it reached 2 publications, then publications in 2018 there was 1 publication, in 2019 it reached 2 publications, then in 2020 there were no published articles, in 2021-2022 there was only 1 publication and the largest number of article publications was in 2023 which reached 5 publications.